Definitely a cracking good crab - New, Straits Times (The New Straits Times Press (M) Berhad, 2010)
The natures gentlest creatures, the horseshoe crab could just be the nations key to breakthrough research into an exclusive multi-million biomedical industry currently dominated by one country. For the past few year, horseshoe crabs or "belangkas" have been subject of intense but low profile research at Universiti Malaysia Terengganu (UMT)